Microencapsulados de extrato de casca de jaboticaba (myrciaria clauliflora) em sistema-modelo de cookie: aspectos físico-químicos e estudo da estabilidade e bioacessibilidade de polifenóis - Aguiar, Lara Louzada (2023)
Jabuticaba peel is one of the fruit fractions that is typically discarded in industries, referred to as a byproduct. Its high content of phenolic compounds, compared to the fruit pulp, makes it promising as a commercial product for the food industry. Therefore, this study aimed to microencapsulate extracts from jabuticaba peel using different drying methods and encapsulating agents to produce powders and incorporate them into cookie model systems, investigating the stability and bioaccessibility of polyphenols. The concentrated jabuticaba peel extract was obtained by ultrasound-assisted extraction using 80% ethanol as the solvent, and microencapsulated using spray drying (SD) and freeze drying (FD), with whey protein isolate (WPI) and gum arabic (GA) as encapsulating agents. The microencapsulated powders were evaluated for their physicochemical characteristics, including moisture, hygroscopicity, solubility, color, encapsulation efficiency, and microstructure, as well as their bioactive compounds (total phenolic content and total anthocyanins) and antioxidant capacity (ABTS, DPPH, and FRAP). After powder characterization, they were incorporated into a cookie model system at concentrations of 10% and 15%, and the stability of color and bioactive compounds was investigated during 3 months of storage, with analysis conducted every 10 days, as well as the bioaccessibility of phenolic compounds. Powders with GA exhibited a tendency towards reddish-yellow color (h° (SD) = 22.79 ± 0.35; h° (FD) = 14.03 ± 0.3), while powders with WPI showed a reddishpurple color (h° (SD) = 359.83 ± 0.00; h° (FD) = 359.93 ± 0.01). In terms of technological properties, the microcapsules produced by FD and WPI stood out, presenting lower moisture (3.01 ± 0.38%) and lower hygroscopicity (8.41 ± 0.99%) when obtained by SD. Powders obtained by FD and GA presented better encapsulation efficiency. Regarding bioactive activity, the microencapsulated xii powders by WPI stood out for having higher levels of phenolic compounds for both drying methods, SD (633.86 mg GAE/100 g) and FD (581.57 mg GAE/100 g). For microencapsulated powders with GA, the best method for preserving antioxidant capacity was SD drying, both for ABTS (3231.81 ± 501.67 μmol TE/100 g), DPPH (2311.90 ± 22.81 μmol TE/100 g), and FRAP (9358.38 ± 335.61 μmol SFE/100 g). Determining the best powder for technological and bioactive parameters, the powders produced with GA obtained by FD stood out with the highest overall desirability value. In the stability study, the cookies showed minimal overall color difference, indicating slight degradation of pigments. Regarding total phenolic content and antioxidant activities, the cookies yielded results proportional to the increase in the concentrations of the added powders. Among them, the cookies supplemented with 15% microcapsules produced by SD and GA exhibited the highest storage stability. Microencapsulation allowed for controlled release of bioactive compounds during digestion, with cookies supplemented with WPI microcapsules showing a higher bioaccessible fraction (377.93 ± 51.88%). Thus, it can be concluded that jabuticaba peels have the potential to be used as sources of microencapsulated bioactives, offering an alternative as food additives.